PENGARUH PROFITABILITAS, RESIKO KEUANGAN DAN PERTUMBUHAN PERUSAHAAN TERHADAP MANAJEMEN LABA PADA PERUSAHAAN KOSMETIK DAN KEPERLUAN RUMAH TANGGA YANG TERDAFTAR DI BURSA EFEK INDONESI TAHUN 2013-2017 - Anna Nubua Hasibuan; Rina Dwiarti (Jurnal Manajemen dan Keuangan, 2019)
This study aims to identify and analyze the effect of Profitability, Financial Risk and Growth on earnings management in cosmetics and household needs companies listed on the Indonesia Stock Exchange (IDX) in 2013-2017. The population used in this study are 6 companies listed on the Indonesia Stock Exchange. The process of determining the sample in this study using purposive sampling so that the number of samples obtained by 5 companies cosmetics and household needs. The type of data used in the research ii is secondary data sourced from the Indonesia Stock Exchange and the analysis technique uses multiple linear regression analysis.The results of this study indicate that partially profitability variables have a negative and not significantly effect on earnings management. Financial risk variables have a negative and not significantly effect on earnings management. The company's growth variable has a negative and not significantly effect on earnings management. The results of the study show that simultaneously the variable profitability, financial risk and company growth have no effect on earnings management.Key Points: Profitability, Financial risk and Company Growth, Profit Management